PWE-151 Emergency ERCP in critically ill patients is a successful procedure. (28th May 2012) - Lekharaju, V P K; Iqbal, J; Noorullah, O; Polavarapu, N; Menon, S; Hood, S; Stern, N; Sturgess, R
Abstract : Introduction: Emergency ERCP may be required in patients with biliary sepsis who rapidly deteriorate with multi-organ dysfunction and cannot wait until the next available list. The majority of these patients require ventilatory and/or inotropic support and general anaesthesia for stabilisation. The data on the outcome of emergency ERCP in this patient cohort is limited. We sought to assess the frequency, indications, and clinical outcomes of emergency ERCPs. Methods: Records of cases undergoing ERCP between November 2008 and November 2011 were retrospectively reviewed. Only patients who were in the intensive care unit requiring ventilatory and/or inotropic support and general anaesthesia for stabilisation at the time of ERCP were included. Data collected included indications, co-morbidities, technical success and 30-day mortality. Results: A total of 2237 ERCPs were performed during this period, out of which 36 (2%) emergency ERCP's were performed in 32 patients. There were 15 males and 17 females. 27/32 patients (84%) had not had previous ERCP. The median age of patients was 79 years (range 42–89). ASA grade prior to the presenting illness was 1 in 6 (17%); 2 in 15 (42%); 3 in 15 (42%). All cases were performed under general anaesthesia in emergency theatre. 27/36 cases (75%) required inotropic support. Indications included cholangitis 28/36 (78%); acute pancreatitis with cholangitis 5/36 (14%); post-operative bile leak 3/36 (8%). Biliary cannulation was achieved in all cases (100%). Endoscopic findings included: common bile duct (CBD) stones in 26/36 (72%); bile leak in 3/36 (8%); CBD stricture in 2/36 (6%); Mirizzi's in 1/36 (3%); blocked plastic stent in 1/36 (3%) and post-sphincterotomy bleed with clot obstruction in 1/36 (3%). Sphincterotomy was performed in 25/36 (69%) cases. 23/36 (64%) patients had stent insertion and in 11/36 (30%) patients balloon trawl was sufficient to clear the ducts. A rapid reduction in bilirubin was observed within 24–48 h following ERCP (Pre ERCP bilirubin: median 104, range 9–553 mmol/l; post ERCP bilirubin: median 29.5 range 12–217 mmol/l p<0.001 (Wilcoxon Signed rank test). 30-day mortality was 25% (8/32 patients) and the majority of these patients (6/8, 75%) died within 24 h of ERCP due to overwhelming sepsis. There was a single case of post sphincterotomy bleed that required a repeat procedure due to clot obstruction. There were no other procedure related complications. The median length of hospital stay was 21 days (range 2–49). Conclusion: Although the 30-day mortality remains high due to multi-organ dysfunction, ERCP is successful in majority of these patients and translates to a good outcome for this cohort of critically ill patients, in whom the prognosis is inevitably poor without an emergency ERCP. Competing interests: None declared.